WAWANCARA DALAM BAHASA MELAYU SAMBAS UNTUK MENGGALI MISKONSEPSI PADA MATERI CAHAYA - Nurhatika, Nurhatika; Sitompul, Stepanus Sahala; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimedto describe forms and causes of misconceptions which are appeared in SD Negeri 3 Karimunting.Survey is used as research method with interview technique 9 student from IV grade in big class were selected as participant sample which is choosen by purposive sampling. Interview About Intances (IAI) technique is used to explore the light concepts particularly to find out the causes of the misconception of students using Sambas Malay language. The results showed misconceptions occurred in all concepts of light, such as the relationship of light to the sense of sight and light can be reflected (9 forms of misconception from 9 students), on the concept of light can propagate straight (3 forms of misconception from 4 students), on the concept of light can penetrate clear objects (3 forms of misconception from 3 students), misconception about refraction of light (6 forms of misconception from 9 students), and misconception about light (13 forms of misconception from 9 students). The causes of misconceptions dominated by students such as pre-conception, associative thought, humanistic thought, learning interest, wrong intuition, incomplete/wrong reasoning, and textbooks. Keywords: Describe, Misconception, Causes, Light